Young People's Development of a Sense of Patriotism during Their Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The modern education system has developed to such an extent that it is difficult to imagine it without modern technologies. In the education system in Uzbekistan, every young learner learns from kindergarten to employment environment. However, as they say, "First upbringing, then education", the love for the motherland should be expressed in the heart of every young learner. In this article, the thoughts of young learners about the content of concepts such as teaching them patriotic ideas during the lesson and respecting the motherland are highlighted.